THE CONCEPT OF ISLAMIC EDUCATION IN THE MORAL DEVELOPMENT OF STUDENTS AT MTS CINA - Yusri Yusri (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to describe in depth the application of the concept of Islamic education in the moral development of students at MTs Cina, Bone Regency. The background of this study is based on the increasing phenomenon of moral crisis among adolescents which is characterized by a decline in the values ​​of honesty, politeness, discipline, and social responsibility. As an Islamic educational institution, MTs has a strategic role in instilling noble moral values ​​to students through an exemplary and habituation approach.This study uses a qualitative approach with a descriptive method. Data collection techniques include observation, in-depth interviews, and documentation. The subjects of the study consisted of the head of the madrasah, aqidah akhlak teachers, al-Qur'an reading and writing teachers, BK teachers, and MTs Cina students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions.The results of the study indicate that the concept of Islamic education is implemented through the dimensions of exemplary behavior, habituation, and moral development with an emphasis on the values ​​of honesty, humility, and patience. Teachers act as good examples in shaping the character of students. Habitual activities such as congregational prayer, tadarus, joint prayer, and instilling social values ​​through extracurricular activities are important means of internalizing Islamic values. However, there are still challenges in the implementation of moral development, such as the negative influence of social media, weak parental supervision, lack of internal awareness of students, and limited madrasah facilities.This study concludes that the concept of Islamic education applied in MTs Cina has proven effective in shaping the character of students, although it requires a sustainable strategy, synergy with families, and improvement of supporting facilities. This finding provides an important contribution in the development of an Islamic education model that emphasizes the integration of spiritual, moral, and social values ​​as the main foundation for the formation of a generation with noble character.